Pregnancy and Birth Cohort Resources in Europe: a Large Opportunity for Aetiological Child Health Research. Issue 4 (17th June 2013) - Larsen, Pernille Stemann; Kamper‐Jørgensen, Mads; Adamson, Ashley; Barros, Henrique; Bonde, Jens Peter; Brescianini, Sonia; Brophy, Sinead; Casas, Maribel; Devereux, Graham; Eggesbø, Merete; Fantini, Maria Pia; Frey, Urs; et al.
Abstract: Background: During the past 25 years, many pregnancy and birth cohorts have been established. Each cohort provides unique opportunities for examining associations of early‐life exposures with child development and health. However, to fully exploit the large amount of available resources and to facilitate cross‐cohort collaboration, it is necessary to have accessible information on each cohort and its individual characteristics. The aim of this work was to provide an overview of European pregnancy and birth cohorts registered in a freely accessible database located at http://www.birthcohorts.net. Methods: European pregnancy and birth cohorts initiated in 1980 or later with at least 300 mother–child pairs enrolled during pregnancy or at birth, and with postnatal data, were eligible for inclusion. Eligible cohorts were invited to provide information on the data and biological samples collected, as well as the timing of data collection. Results: In total, 70 cohorts were identified. Of these, 56 fulfilled the inclusion criteria encompassing a total of more than 500 000 live‐born European children. The cohorts represented 19 countries with the majority of cohorts located in Northern and Western Europe. Some cohorts were general with multiple aims, whilst others focused on specific health or exposure‐related research questions. Conclusion: This work demonstrates a great potential for cross‐cohort collaboration addressing important aspects of child health. The web site, http://www.birthcohorts.net, proved to be a useful tool for accessing information on European pregnancy and birth cohorts and their characteristics.